Evaluation of Physical Properties and Shelf - Life Test of Herbal Deodorant Spray Preparation Based on Bidara Leaf Infusion (Ziziphus Mauritiana L.) - Miladea Istikhoroh; Heru Nurcahyo; Inur Tivani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Deodorant is a topical preparation used to help reduce body odor caused by bacterial activity on the skin, such as Staphylococcus epidermidis. Along with the increasing interest in natural-based products, bidara leaves (Ziziphus mauritiana L.) have the potential to be used as an active ingredient due to their antibacterial activity. This study aims to formulate a herbal deodorant spray containing bidara leaf infusion and to evaluate its physical characteristics and stability. Bidara leaf infusion will be prepared using the infusion (inundation) method and formulated into a deodorant spray in three different concentrations, namely 5%, 10%, and 15%. The formulated deodorant sprays will be evaluated through organoleptic test, pH, homogeneity, clarity, and spray volume. Quantitative data will be analyzed using One-Way ANOVA, while organoleptic data will be analyzed descriptively. Stability testing will be conducted at room temperature and analyzed using Repeated Measures ANOVA if the parametric requirements are fulfilled.